2019
DOI: 10.1016/j.jcot.2019.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anatomic risk factors using magnetic resonance imaging in non-contact anterior cruciate ligament injury

Abstract: Background: The purpose of our study was to compare the significance of the tibio-femoral morphological variables (notch width index, notch shape index, intercondylar notch angle, medial and lateral tibial slopes) in predicting non-contact ACL (anterior cruciate ligament) injuries and to compare these factors between genders in South Asian population. The author hopes to provide a comprehensive analysis on the risk factors which would help in betterment of the patients at danger for anterior cruciate ligament … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
2
5
1
Order By: Relevance
“…Therefore, they considered the intercondylar angle a more useful parameter for describing the narrow intercondylar notch [ 39 ]. A similar result was concluded by Raja et al [ 40 ]. In this study, we found intercondylar angle did not associate with meniscal injury.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, they considered the intercondylar angle a more useful parameter for describing the narrow intercondylar notch [ 39 ]. A similar result was concluded by Raja et al [ 40 ]. In this study, we found intercondylar angle did not associate with meniscal injury.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, they considered the intercondylar angle as a more useful parameter to describe the narrow intercondylar notch (39). A similar result was concluded by Raja et al (40). In this study, we found intercondylar angle did not associate with meniscal injury.…”
Section: Discussionsupporting
confidence: 88%
“…Some investigators [12,13] find no correlation between the rate of ACL graft rapture and the PTS values. This is in contrast with the findings that further ACL injury may be affected by the medial tibial slope, the lateral tibial slope, or both [8][9][10][11][14][15][16][17].…”
Section: Introductioncontrasting
confidence: 91%